Far From Home: An Examination of the Juvenile Visitation Experience and the Barriers to Getting There. (June 2019) - Young, Brae Campion; Nadel, Melissa R.; Bales, William D.; Pesta, George B.; Greenwald, Mark A.
Despite a growing body of research on prison visitation, very few studies have examined visitation among committed juvenile offenders. As a result, we have little understanding of how youth experience visits and why some never receive them. This article fills these gaps. Using surveys collected from 1, 202 youth released from residential facilities in Florida, we found that among youth who were visited, they had positive experiences with visits and that families went to great lengths to visit. For those youth who were not visited, the most common barrier was distance from home. However, some youth were not visited because they refused visits or because families withheld visits as punishment. Moreover, despite the possibility that lack of visitation is harmful, we found that most not-visited youth had positive perceptions of their future success. Policy implications and directions for research are discussed.